Influence of impulse magnetic fields of extremely low frequencies on H2O2- and Fe2+-induced free radical lipid oxidation in liposomal suspensions - V. S. Martynyuk; Yu. V. Tseyslyer (Біофізичний вісник, 2022)
Background: For a long time, special attention in experimental biology and medicine is paid to free radical processes involving reactive oxygen species. In electromagnetic biology, the interest in free radical oxidation in biological membranes has increased significantly due to the discovery of spin mechanisms of magnetic fields on free radical processes. In the present day, these mechanisms are considered to be key in the processes of magnetoreception in living organisms. Liposomes, as the simplest models of biological membranes, are often used to study the primary mechanisms of action of different factors on the structural and functional properties of membranes. However, the influence of ecological significant extremely low-frequency magnetic fields on free radical oxidation in liposomal suspensions has not been studied enough.